The Impact of Green Technology and Health Expenditure on Life Expectancy in Malaysia - Amri Sulong; Mohd Shahidan Shaari; Abdul Ekhmal Danial Abdul Halim (Journal of Techno-Social, 2024)
This study investigates the dynamic interactions between green technology, health expenditure, and life expectancy in Malaysia, employing short-run and long-run Autoregressive Distributed Lag (ARDL) tests. In the short run, while the natural logarithm of health expenditure (LNHE) and gross domestic product (LNGDP) exhibit positive coefficients, suggesting potential relationships, statistical significance is not established at the conventional 0.05 level. However, the negative coefficient for the real exchange rate (LNRE) indicates a statistically significant negative relationship with life expectancy. In the long run, positive and negative coefficients for LNHE and LNGDP, respectively, lack statistical significance. LNRE suggests potential significance just beyond the conventional threshold. The model explains a substantial proportion of variance in the dependent variable, but caution is advised due to potential overfitting. These findings emphasize the intricate nature of these relationships, prompting a careful interpretation and highlighting the need for further analyses and data exploration to fortify conclusions. The implications contribute to policy discussions on utilizing green technology and optimizing health expenditure to enhance life expectancy, emphasizing a comprehensive approach to sustainable development in Malaysia.